Addictive Parameter In Ensemble Technique & Implementation Using Flask Server - et. al., G.Baby Saral, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Exceeding use of screen has completely switched the teens routine life who are addicted with social media and other electronic accessories, which results in psychological disorder like anger, stress, depression, anxiety etc., The addiction data set applied with some algorithm like Random forest, decision tree and so on. The Ensemble Technique bagging and voting classifier are used for better prediction. The bagging classifier which combines the decision tree and random forest, the voting classifier which compares the bagging classifier and gradient booster. Among the two classifier bagging classifier gives the best prediction result. Implementation proceeded with webpage, Flask server and python model using logistic regression model. In future the app can be used as a standalone system, which now works in local server.